Dark shadows [videorecording (DVD)] - Burton, Tim, 1958-; Pfeiffer, Michelle, 1957-; Depp, Johnny; Bonham Carter, Helena, 1966- (Warner Bros., 2012)
Imprisoned vampire, Barnabas Collins is inadvertently freed from his tomb and emerges into the very changed world of 1972. He returns to Collinwood Manor to find that his once-grand estate has fallen into ruin. The dysfunctional remnants of the Collins family have fared little better and are in need of his protection.